The Social and Material Life of Antimicrobial Clay: Exploring Antimicrobial Resistance, Medicines' Materiality, and Medicines Optimization - Jamie, Kimberly; Sharples, Gary (Frontiers in Sociology, 2020)
While sociologists have made significant theoretical contributions to the antimicrobial resistance (AMR) debate, little attention has been given to the antimicrobial products themselves. Here we advocate a significant new direction which centres on the social and material life of antimicrobials, specifically on what they are made from and how this affects their use. This focus is timely because, in the context of declining efficacy of biomedical antibiotics, diverse materials are increasingly taking centre stage in research and drug discovery as potential agents for new antimicrobial treatments. Of particular significance are natural antimicrobials, such as plants, honey and clay, whose antimicrobial potential is well-documented and which are increasingly moving into mainstream antimicrobial research. Alongside this biomedical focus, we suggest that the social and material lives of these antimicrobial materials require attention to (i) highlight the ways they have been, and continue to be, used in diverse cultures globally, (ii) explore ways we might theorise these materials within wider AMR debates, and (iii) examine the impact of antimicrobials’ materiality on their use by patients. This article takes the example of clay, whose antimicrobial properties are well-established and which has been used to treat wounds and gastrointestinal problems for millennia. We first locate clay as an exemplar of a wider shift towards natural products drug discovery in pharmaceutical science and antimicrobial research. We then offer a number of theoretical ‘ways in’ for sociologists to begin making sense of clay as it comes under the western biomedical gaze. We map these conceptual lenses on to clay’s physical and symbolic mobility from its use in the global south into western biomedical research and commercialisation. We particularly concentrate on post-colonial theory as a means to understand clay’s movement from global south to north; laboratory studies to examine its symbolic transformation to a black-boxed antimicrobial artefact; and valuation practices as a lens to capture its movement from the margins to the mainstream. We finish by reflecting on the importance of materiality in addressing optimal use of medicines and by advocating an interdisciplinary approach to AMR which positions sociology as a key contributor to AMR solutions.